Hydrotalcite precursor-based catalyst with improved performance for LTS reactions
By using amorphous Cu-Zn-Al mixed oxide catalyst in the LTS reaction, the shortcomings of existing catalysts in CO conversion and stability are solved, and more efficient catalytic performance is achieved.
Patent Information
- Application Number
- CN202380045123.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-03-15
- Publication Date
- 2025-01-14
AI Technical Summary
There is room for improvement in the CO conversion and stability of existing low-temperature water gas conversion (LTS) catalysts, especially compared with high-temperature catalysts, their inactivation behavior is more obvious.
A Cu-Zn-Al hydroxide-carbonate precipitate was formed by mixing an aqueous solution of Cu, Zn and Al compounds with a carbonate solution, and calcined within a range of 200-600°C to obtain amorphous Cu-Zn- Al mixed oxide catalyst for LTS reaction.
It improves the CO conversion rate in LTS reaction, reduces the deactivation behavior of the catalyst, and provides more efficient catalytic performance.
Smart Images

Figure CN119317485A_ABST
Abstract
Description
[0001] This invention relates to a novel catalyst for LTS reactions, its preparation method, and the LTS reaction performed using the catalyst. Background of the Invention
[0002] Syngas plays an important role as a feedstock not only for the production of many basic chemicals (such as methanol or ammonia) but also for the production of hydrogen.
[0003] To adjust the concentrations of CO, CO2, and H2 in the syngas feedstock to optimal levels for their commercial use in different reactions, water-gas shift reaction is typically employed.
[0004] Commercially, two types of water-gas shift reactions are typically employed: high-temperature shift (HTS) reactions are usually carried out at higher temperatures in the range of 350–400 °C, while low-temperature shift (LTS) reactions occur at lower temperatures in the range of 150–250 °C, as exemplarily disclosed by C. Ratnasamy et al., Catalysis Reviews, 51:325–440, 2009.
[0005] US 6,693,057 B1 discloses a copper / zinc / aluminum LTS catalyst. The catalyst is formed from a precursor comprising aluminum in the form of a hydrotalcite and aluminum separated from the hydrotalcite.
[0006] CN 105214671 A describes the preparation of a Cu / ZnAl2O4 LTS catalyst, wherein the catalyst comprises an active component and a support, wherein the active component is copper, the support is Cu / ZnAl2O4, and the copper content is 10-40% by weight. A Cu-Zn-Al hydroxide intermediate synthesized by a co-precipitation method is used as a precursor, wherein a solution containing Cu, Zn, and Al compounds is added to a carbonate-containing solution.
[0007] JP 2009241036 A relates to the preparation of a water-gas shift catalyst by combining a Cu-Zn-Al solution with an alkaline solution. The resulting catalyst exhibits a unique X-ray diffraction pattern.
[0008] Despite the commercialization of many types of LTS catalysts over the decades, there remains a need for LTS catalysts that exhibit improved catalytic behavior compared to existing technology catalyst types.
[0009] Therefore, the object of the present invention is to provide a catalyst for LTS reactions, characterized by improved CO conversion and reduced deactivation behavior when used in LTS reactions.
[0010] This objective is achieved through a catalyst used for the LTS reaction, which comprises an amorphous Cu-Zn-Al mixed oxide.
[0011] The catalyst of the present invention can be obtained by a method comprising the following steps:
[0012] a) Provide an aqueous solution containing dissolved Cu, Zn, and Al compounds.
[0013] b) Provide an alkaline aqueous solution containing carbonates.
[0014] c) Mix the solution obtained in step a) and the carbonate solution obtained in step b) to obtain a mixture containing a precipitate of mixed Cu-Zn-Al hydroxide-carbonate.
[0015] d) The mixture obtained after aging step c).
[0016] e) Separate the precipitate from the solution and optionally wash and / or dry the precipitate.
[0017] f) Calcination of the precipitate at a temperature ranging from 200 to 600 °C for a duration ranging from 0.5 h to 6 h.
[0018] The aqueous solution of copper, zinc, and aluminum compounds is, for example, produced by dissolving at least one copper compound, at least one zinc compound, and at least one aluminum compound in an aqueous solution, wherein the aqueous solution can be water, preferably deionized water, having a pH of 7, or an acidic aqueous solution. Nitric acid solution is used as a preferred acidic aqueous solution. In a preferred embodiment, the aqueous solution containing dissolved Cu, Zn, and Al compounds is an acidic solution.
[0019] In principle, any copper, zinc, and aluminum compound soluble in water or acidic solutions may be selected, such as their corresponding metals, oxides, or metal salts. Preferably, the copper, zinc, and aluminum compounds are selected from their corresponding oxides, carbonates, hydroxides, hydroxocarbonates, halides such as chlorides, bromides, and / or iodides, nitrates, and / or sulfates.
[0020] Preferred copper compounds are copper oxide (Cu2O and / or CuO), copper nitrate, copper chloride, copper carbonate, copper hydroxycarbonate (x·CuCO3·Cu(OH)2, where x can be 1 or 2), copper acetate, and copper sulfate, especially copper nitrate.
[0021] Preferred zinc compounds are zinc oxide (ZnO), zinc nitrate, zinc chloride, zinc carbonate, zinc hydroxycarbonate (x·ZnCO3·Zn(OH)2, where x can be 1 or 2), zinc acetate, and zinc sulfate, especially zinc nitrate or zinc oxide.
[0022] Preferred aluminum compounds are aluminum nitrate, aluminum hydroxide, hydrated alumina (boehmite), aluminum chloride, alkali metal aluminates and alumina (Al2O3), especially aluminum nitrate or sodium aluminate.
[0023] The dissolution of at least one copper compound, at least one zinc compound, and at least one aluminum compound can be accomplished either in a common solution or alternatively by dissolving the compounds in at least two separate dissolution media. In one embodiment, at least one copper compound is dissolved in an aqueous solution, while at least one zinc compound and at least one aluminum compound are dissolved in a common aqueous solution. In another embodiment, at least one aluminum compound is dissolved in a separate aqueous solution, while at least one copper compound and at least one zinc compound are dissolved in a common aqueous solution. The separate solutions (if present) are combined prior to precipitation in step c) to produce a solution containing the dissolved Cu, Zn, and Al compounds.
[0024] An aqueous solution containing carbonates can be produced by dissolving or suspending at least one alkali metal carbonate (e.g., lithium carbonate, sodium carbonate, potassium carbonate, rubidium carbonate, or cesium carbonate) or ammonium carbonate, or a mixture thereof, in water. Similarly, the corresponding bicarbonate or any mixture of carbonate and bicarbonate can be used with or in place of the carbonate. Alkali metal carbonates or ammonium carbonate are preferred. In one embodiment, in addition to the carbonate, an alkali metal hydroxide or alkaline earth metal hydroxide, or a corresponding solution, is added. The pH of the carbonate-containing solution is greater than 7, preferably 8 or higher, more preferably 9 or higher.
[0025] In step c), the metal-containing solution and the carbonate-containing solution are mixed to obtain a mixture containing a precipitate of mixed Cu-Zn-Al hydroxide-carbonate. This mixing can be accomplished by adding the carbonate-containing solution to the metal-containing solution. This addition causes the pH of the metal-containing solution provided in step a) to increase to a pH of 7.5 or higher, preferably 8.0 or higher, more preferably 8.5, and most preferably 9. If the pH exceeds 9, the pH can be adjusted to 7.5 to 9, preferably 8.0 to 9, more preferably 8.5 to 9, and most preferably 9, by adding additional acid to the mixture obtained in step c). In another embodiment, the metal-containing solution and the carbonate-containing solution are added together to another solution, preferably water. In yet another embodiment, the two solutions can be added together to an aqueous container where the pH can be controlled at a certain level. This joint addition causes the pH of the solution in the container to increase to a pH of 7.5 or higher, preferably 8.0 or higher, more preferably 8.5, and most preferably 9. If the pH value exceeds 9, the pH can be adjusted to 7.5 to 9, preferably 8.0 to 9, more preferably 8.5 to 9, and most preferably 9, by adding additional acid to the mixture obtained in step c).
[0026] Combining an aqueous solution of dissolved Cu, Zn, and Al compounds with an aqueous solution containing carbonates results in the formation of a precipitate. The precipitate is separated, optionally washed and / or dried, and subsequently calcined and optionally shaped into a shaped catalyst body.
[0027] In one embodiment, an aqueous solution of at least one Cu, Zn and Al compound is heated to a temperature above 30°C, for example, to a temperature in the range of 50°C to 90°C, particularly to a temperature in the range of 60°C to 85°C.
[0028] In another embodiment, at least one carbonate-containing solution is heated to a temperature above 30°C, for example, to a temperature in the range of 50°C to 90°C, particularly to a temperature in the range of 60°C to 85°C.
[0029] In another embodiment, both an aqueous solution of at least one dissolved Cu, Zn and Al compound and at least one carbonate-containing solution are heated to a temperature in the range of 50°C to 90°C, particularly to a temperature in the range of 60°C to 85°C.
[0030] In a preferred embodiment, an aqueous solution of at least one Cu, Zn and Al compound and at least one carbonate-containing solution are kept at a temperature of up to 30°C, preferably up to 25°C, before combination.
[0031] When an aqueous solution of at least one dissolved Cu, Zn, and Al compound is combined with an aqueous solution containing at least one carbonate, a precipitate forms in the mixture. The combination of solutions is generally carried out in a stirred vessel. The vessel is preferably stirred using a tilting blade agitator, a propeller agitator, or other commercially available agitators.
[0032] After the complete combination of an aqueous solution of at least one Cu, Zn and Al compound and at least one carbonate-containing solution and during step d), the pH of the mixture is preferably maintained in the range of 7.5 to 9, preferably in the range of 8.0 to 9.0, and most preferably in the range of 8.5 to 9.0.
[0033] In step d), the mixture obtained after step c) is subjected to an aging process. Here, storage lasts from 5 minutes to 3 hours without the addition of any additional components. During step d), the mixture may be kept in motion or stored without any stirring. The aging temperature typically corresponds to the ambient temperature of the mixture, but can be set in a controlled manner within the range of 0°C to 90°C.
[0034] In step e), the precipitate is separated from the solution. The precipitate is preferably separated by filtration. Alternatively, it can be separated by decantation or centrifugation.
[0035] Prior to calcination, and optionally prior to drying, the separated precipitate may optionally undergo one or more washing steps. Here, a filter press may first be used to separate the solution mixture containing the precipitate from the precipitate, and then water may be passed through the material in the filter press to wash the material. Alternatively, after removing the solution mixture containing the precipitate by filtration, decantation, or centrifugation, the separated precipitate may be slurried in a container and subsequently separated from the liquid phase again by means of a filter press, centrifuge, or decanter. This operation is generally performed once or multiple times until the filtrate reaches a specific conductivity. Here, conductivity is related to the concentration of dissolved ions. The conductivity of the filtrate from the final washing operation is preferably 0.5 mS / cm or lower, particularly 0.2 mS / cm or lower. Conductivity is determined according to DIN 38404, Part 8.
[0036] In one embodiment, the precipitate separated and optionally washed in step e) is dried. This drying can be performed, for example, by spray drying. For this purpose, water is used to produce a suspension from the separated precipitate (e.g., filter cake) having a solids content typically between 10 and 40% by weight. In one embodiment, this suspension is then fed into a spray dryer via a nozzle. The outlet temperature of the dryer is preferably in the range of 75°C to 130°C, more preferably in the range of 90°C to 120°C, and is typically controlled by parameters such as the amount of suspension sprayed, the solids content of the suspension (and therefore the amount of water to be evaporated), or the temperature in the spray dryer. Processing materials by spray drying specifically produces a powder having an H2O content of up to 30% by weight, preferably up to 20% by weight, more preferably up to 10% by weight.
[0037] In another embodiment, drying is carried out in a box dryer, rotary dryer, belt dryer, or cyclone flash dryer. The temperature during drying is preferably in the range of 75°C to 130°C, more preferably in the range of 90°C to 120°C. The duration is preferably in the range of 30 minutes to 15 hours.
[0038] The precipitate obtained after step e) is characterized by the presence of Cu, Zn, and Al in the form of a hydrotalcite structure as determined by powder XRD. In a preferred embodiment, the precipitate contains less than 10% by weight, preferably less than 5% by weight, of Cu, Zn, and Al compounds other than the hydrotalcite structure determined by powder XRD. In a more preferred embodiment, the precipitate exhibits only the hydrotalcite structure determined by powder XRD.
[0039] In step f), the resulting precipitate is subjected to a calcination step, wherein the temperature is in the range of 200°C to 600°C, preferably in the range of 200°C to 500°C, more preferably in the range of 300°C to 500°C, and most preferably in the range of 350°C to 500°C. The calcination duration is in the range of 15 minutes to 8 hours, preferably 30 minutes to 6 hours, more preferably 1 hour to 6 hours. Calcination can be carried out in air or under a protective gas (e.g., argon or nitrogen), or under oxygen or a mixture thereof. Calcination can be carried out intermittently, for example in a disc furnace, or continuously, for example in a swirl furnace.
[0040] Based on the total weight of the calcined precipitate obtained in step f), the calcined precipitate obtained after step f) has a carbonate content of 10% or less by weight, preferably 7% or less by weight, and more preferably 0.5 to 6% by weight (determined by the CO2 content released).
[0041] According to conventional X-ray diffraction, the calcined precipitate obtained after step f) is characterized by comprising an amorphous Cu-Zn-Al mixed oxide. In the context of this invention, the amorphous Cu-Zn-Al mixed oxide is in solid form, and its powder XRD pattern does not contain Bragg reflections associated with the Cu-Zn-Al mixed oxide or any Cu, Zn, and / or Al compounds. This material does not exhibit long-range atomic order or periodicity in conventional X-ray diffraction patterns.
[0042] In addition, through distribution function (PDF) analysis, the calcined precipitate obtained after step f) contains CuO, ZnO and Zn spinel, preferably the structural domains of Zn spinel with zinc spinel structure.
[0043] The calcined precipitate obtained in step f) can be used as a catalyst or subsequently shaped in step g) to obtain a shaped catalyst body. Shaping methods include tableting, granulation, or extrusion. The catalyst body can exist in various forms, such as spheres, cylinders, or hollow spheres, such as rings. Preferred shaping method is tableting. Tableting is preferably performed using a tablet press, such as a Korsch tablet press. Tableting allows for the production of tablets having a diameter of 1 to 20 mm, preferably 2 to 10 mm, and most preferably 3 to 5 mm, and a height of 1 to 10 mm, preferably 2 to 10 mm, and most preferably 3 to 5 mm. Specifically, tablets are produced having a side crush strength of 40 to 250 N, preferably 80 to 220 N, more preferably 100 to 220 N, and most preferably 150 to 210 N. The tablets preferably have a diameter in the range of 3 to 5 mm, a height in the range of 3 to 5 mm, and a side crush strength in the range of 150 to 210 N.
[0044] Precipitation is preferably carried out with the addition of a lubricant such as graphite, oil, or stearate / ester, preferably graphite. Here, the precipitate obtained in step f) is mixed with a lubricant, particularly graphite, optionally compacted and / or granulated, and then tableted. Prior to tableting, a lubricant is preferably added in an amount ranging from 0.1% to 8% by weight, preferably from 1.0% to 3.0% by weight, based on the total weight of the composition to be tableted.
[0045] In another embodiment, the shaped body obtained in step g) is subjected to additional heat treatment in step h). Such heat treatment is carried out at temperatures between 150°C and 500°C, preferably between 200°C and 500°C, and most preferably between 300°C and 450°C. The heat treatment can be carried out intermittently or continuously, for example in a belt furnace or a disc furnace. It is preferably carried out in air or under a protective gas (e.g., argon or nitrogen), or in oxygen or a mixture thereof. The heat treatment is preferably carried out over a period of 30 minutes to 8 hours, preferably over a period of 1 to 6 hours.
[0046] For the calcined flakes, the residual loss on ignition of the catalyst of the present invention at 900°C is 13% or less by weight, preferably 10% or less by weight, more preferably 5% or less by weight, and most preferably 7% or less by weight.
[0047] In another embodiment, the shaped catalyst body obtained from step g) or h) is reduced in step i).
[0048] Reduction is preferably performed by heating a shaped catalyst body in a reducing atmosphere or by calcining a shaped catalyst body. In one embodiment, the reducing atmosphere is hydrogen or a mixture of hydrogen and nitrogen. In another embodiment, the reducing atmosphere is syngas. Reduction is carried out at a temperature in the range of, for example, 150°C to 450°C, particularly in the range of 180°C to 250°C, and preferably in the range of 190°C to 210°C. Reduction is carried out over a period of time, for example, from 1 hour to 10 days, preferably from 2 hours to 72 hours, and more preferably from 24 to 48 hours. In a preferred embodiment, reduction is carried out at a temperature in the range of 190°C to 210°C over a period of 24 to 48 hours.
[0049] Following reduction, the formed catalyst body is preferably wet-stabilized or dry-stabilized. In the case of wet stabilization, the formed body is covered with a liquid to minimize contact with oxygen. Suitable liquids include organic liquids and water, with organic liquids being preferred. Preferred organic liquids are those having a vapor pressure of 0.5 hPa or lower at 20°C. Examples of suitable organic liquids are isodecanol, Nafol, fatty alcohols, hexadecane, 2-ethylhexanol, propylene glycol, and mixtures thereof, particularly isodecanol.
[0050] In the case of dry stabilization, a mixture of oxygen or an oxygen-containing gas (preferably air) and an inert gas (e.g., argon or nitrogen) is introduced into the reduction reactor. The oxygen concentration in the mixture is preferably increased from 0.04% by volume to 21% by volume. For example, a mixture of air and an inert gas can be introduced, wherein the air-to-inert gas ratio is initially 0.2% by volume to 99.8% by volume of inert gas. The air-to-inert gas ratio is then gradually increased (e.g., continuously or stepwise) until, for example, 100% by volume of air (corresponding to an oxygen concentration of approximately 21% by volume) is finally introduced. Without being bound by any theory, it is assumed that the introduction of air or oxygen results in the formation of a thin oxide layer on the catalyst surface with a thickness of, for example, 0.5 to 50 nm, preferably 1 to 20 nm, particularly 1 to 10 nm, and that this thin oxide layer protects the catalyst from further oxidation. In the case of dry stabilization, the reactor temperature is preferably 100°C or lower, more preferably 20°C to 70°C, and most preferably 30°C to 50°C. After this stabilization, the catalyst can be transported to the user / equipment operator. Stabilization is not required when the catalyst user performs step i) in situ in the reactor.
[0051] The shaped catalyst bodies are characterized by comprising amorphous Cu-Zn-Al mixed oxides. In addition to the amorphous Cu-Zn-Al mixed oxides, the shaped catalyst bodies may contain other compounds such as lubricants or additives, exhibiting Bragg reflection.
[0052] In another embodiment, distribution function (PDF) analysis determines that the formed catalyst body further comprises CuO, ZnO, and Zn spinel, preferably Zn spinel with a zinc spinel structure. In one embodiment, the PDF determines that the CuO phase content, in weight percentages (wt%), is in the range of 10 to 20, preferably 15 to 20; the ZnO phase content, in weight percentages (wt%), is in the range of 1 to 10, preferably 2 to 7; and the Zn spinel phase content, in weight percentages (wt%), is in the range of 70 to 89, preferably 75 to 85.
[0053] The amount of Cu in the catalyst is in the range of 30 to 50 mol%, preferably 30 to 45 mol%, relative to the total amount of Cu, Zn and Al in the catalyst.
[0054] The amount of Zn in the catalyst is in the range of 15 to 45 mol%, preferably 20 to 40 mol%, relative to the total amount of Cu, Zn and Al in the catalyst.
[0055] The amount of Al in the catalyst is in the range of 15 to 50 mol%, preferably 20 to 40 mol%, relative to the total amount of Cu, Zn and Al in the catalyst.
[0056] The molar ratio of Cu to Zn in the catalyst is in the range of 2.5 to 1.0, preferably 2.1 to 1.1.
[0057] In one embodiment, the catalyst according to the invention comprises at least one promoter compound. The at least one promoter compound is preferably selected from alkali metals, preferably K, Rb, or Cs; alkaline earth metals, preferably Mg; rare earth metals, preferably La or Ce; Ga, In, Si, V, Mn, Fe, Co, Y, or Zr compounds and mixtures thereof. At least one promoter may be included in the formed catalyst body of the invention in the form of a metal oxide of one of the aforementioned metals. The metal oxide may comprise one or more oxides of the aforementioned metals. Based on the total weight of the catalyst, at least one promoter compound is present in the catalyst in an amount ranging from 0.1 to 12% by weight, preferably from 1 to 7% by weight, more preferably from 3 to 5% by weight.
[0058] In one embodiment, at least one promoter compound (preferably selected from rare earth metals, preferably La or Ce, Ga, In, Si, V, Mn, Fe, Co, Y or Zr compounds and mixtures thereof) is added to the solution containing dissolved Cu, Zn and Al compounds in step a) and co-precipitated in step c). In another embodiment, at least one promoter compound (preferably selected from alkali metal or alkaline earth metal compounds and mixtures thereof) is added to the precipitate or formed catalyst body by impregnation, initial wetting, or by mixing the precipitate with the promoter compound.
[0059] The catalyst of the present invention preferably has 60 m 2 / g to 200 m 2 Within the range of / g, 75 m is preferred. 2 / g to 180 m 2 / g, optimal value 100 m 2 / g to 180 m 2 BET surfaces within the range of / g.
[0060] In one embodiment, the shaped catalyst body has a diameter of 200 to 500 mm. 3 / g, preferably 250 to 450 mm 3 / g, with an optimal value of 280 to 430 mm 3 Pore volume within the range of / g.
[0061] In one embodiment, the lateral crushing strength of the formed catalyst body is in the range of 40 to 250 N, preferably 80 to 220 N, more preferably 100 to 220 N, and most preferably 150 N to 210 N.
[0062] In another embodiment, the side crushing strength of the reduced and shaped catalyst body is in the range of 10 N to 220 N, preferably 40 N to 220 N, and more preferably 80 N to 160 N.
[0063] The catalyst of this invention is suitable for use in a wide range of reactions. Potential reactions include water-gas shift reactions, particularly LTS reactions, ester hydrolysis, and the hydrogenation of fatty acid esters.
[0064] In a preferred embodiment, the catalyst obtained by the method according to the invention can be used in a water-gas shift reaction, preferably a low-temperature shift (LTS) reaction, carried out using a syngas composition comprising CO, CO2, and H2. In one embodiment, the CO content of the syngas is 60% or less, preferably 20% or less. In another embodiment, the CO content is 0.1% or more. In a preferred embodiment, the CO content is in the range of 0.1% to 60%, preferably in the range of 0.1% to 20%.
[0065] The temperature is typically in the range of 150 to 250°C, preferably in the range of 160 to 240°C, and more preferably in the range of 170 to 230°C.
[0066] The pressure is typically in the range of 1 to 50 bar, preferably in the range of 1 to 30 bar, and more preferably in the range of 1 to 25 bar.
[0067] The catalyst is typically reduced before being used in the LTS reaction according to the invention.
[0068] The following examples illustrate specific embodiments of the invention in more detail.
[0069] Figure 1 The CO conversion rates of the catalysts according to Examples 1 to 3 and Comparative Examples 1 and 2 are shown at different temperatures.
[0070] Figure 2 The CO conversion rates of the catalysts according to Examples 4 to 6 and Comparative Examples 1 and 2 are shown at different temperatures.
[0071] method
[0072] Bulk density
[0073] The bulk density of the formed catalyst body was determined as follows: a 100 mL graduated cylinder was completely filled with the catalyst sample. The bulk density was calculated by dividing the weight of the catalyst filled into the graduated cylinder by the volume of 100 mL.
[0074] Loss on ignition
[0075] For the purposes of this invention, the loss on ignition is determined as follows: approximately 1-2 g of a sample of the material to be analyzed is weighed, and then the sample is heated at room temperature to 900°C and maintained at that temperature for 3 hours. The sample is then cooled under a protective atmosphere, and the remaining weight is measured. The difference between the weight before and after heat treatment corresponds to the loss on ignition.
[0076] Lateral crushing strength
[0077] The lateral crushing strength of shaped catalyst bodies is determined according to ASTM D4179-11, without preheating of the samples. Here, a statistically sufficient number of pieces (at least 20 pieces) are measured, and the arithmetic mean of the individual measurements is calculated. This arithmetic mean corresponds to the lateral crushing strength of a particular sample. The same method is applied to reduced shaped catalyst bodies, wherein the sample is reduced in a mixture of hydrogen and nitrogen prior to measurement, and the sample is held under nitrogen during measurement.
[0078] Elemental analysis
[0079] Chemical elements are determined by ICP (inductively coupled plasma) measurement according to DIN EN ISO 11885.
[0080] BET surface area
[0081] The BET specific surface area is determined by nitrogen adsorption according to DIN 66131. The catalyst obtained by the method of the present invention preferably has a BET surface area in the range of 20 to 100 m² / g, particularly 30 to 80 m² / g, and especially preferably 40 to 60 m² / g.
[0082] Pore volume
[0083] The pore volume of the formed catalyst body is measured by mercury porosity determination according to DIN 66133.
[0084] Structure determined through PDF analysis
[0085] The local structure was determined by PDF analysis as follows: First, the variable counting time (VCT) method was used, followed by molybdenum radiation (Q) max 17.5 Å -1XRD data of the calcined material and an empty capillary (for reference) were measured in transmission mode using an Empyrean diffractometer (1 mm diameter capillary). PDF data from the recorded XRD data were generated using Malvern PanalyticalHighScore Plus software. The experimental PDF data were analyzed using the PDFgui program by fitting the observed PDF data to calculated data generated from the model structure (.cif file) in PDFgui. The contribution of the empty capillary was subtracted from the background of the observed data before fitting. Instrument-related parameters such as peak broadening (Qbroad) and peak suppression (Qdamp) factors were determined by analyzing the PDF of a standard crystalline powder (measured in the same manner as the sample), and these factors were kept constant throughout the data fitting process. The cell parameters and atomic displacement parameters of each phase were progressively refined.
[0086] Wear and tear
[0087] Wear loss was determined as follows: For a sample of approximately 110 g, any fine particles were first separated using a 1 mm sieve, and then the sample was heat-treated at 120°C for 3 hours and weighed.
[0088] A 100 g sample was then placed in a closed steel drum and rotated 1800 times at 60 rpm. The sample was then placed through a 1 mm sieve and separated from any fine particles. Finally, the sample was heat-treated again at 120°C for 3 hours and weighed. Wear loss was calculated as the difference between the initial and final weight, divided by the initial weight. Example
[0089] Precursor A
[0090] Dissolve 1.725 kg of sodium aluminate and 0.565 kg of zinc oxide in 4.5 L of deionized water containing 9.031 kg of concentrated nitric acid. Add the resulting solution to a solution of 2.727 kg of Cu(NO3)2·2.5 H2O dissolved in 4 L of deionized water. Then mix the resulting solution with additional deionized water to obtain a total volume of 20 L.
[0091] The precipitation solution was prepared by dissolving 1.136 kg NaCO3 in 20 L of deionized water, then adding 3.000 kg of saturated sodium hydroxide solution and filling the volume to 30 L with deionized water.
[0092] The metal-containing solution and the precipitate solution were then added dropwise to a batch containing 15 L of deionized water, rapidly increasing the pH to pH 9. This pH was maintained during the addition, and a blue suspension began to form. Once the addition of the metal-containing solution was complete, the addition of the precipitate solution was stopped, and the resulting blue suspension was stirred at room temperature for an additional hour. The precipitate was removed from the suspension by filtration on a box filter press. The filter cake was washed with deionized water until the filtrate had a conductivity of <250 µS / cm. This filter cake was used to prepare the catalyst samples of Examples 1 to 3. It showed a Cu content of 31.6 mol%, a Zn content of 18.7 mol%, and an Al content of 49.8 mol%.
[0093] Precursor B
[0094] 1.337 kg of sodium aluminate and 0.576 kg of zinc oxide were dissolved in 4.5 L of deionized water containing 7.007 kg of concentrated nitric acid. The resulting solution was then added to a solution of 3.422 kg of Cu(NO3)2·2.5 H2O dissolved in 4 L of deionized water. The resulting solution was then mixed with additional deionized water to obtain a total volume of 20 L.
[0095] The precipitation solution was prepared by dissolving 1.136 kg NaCO3 in 20 L of deionized water, then adding 3.500 kg of saturated sodium hydroxide solution and filling the volume to 30 L with deionized water.
[0096] The metal-containing solution and the precipitate solution were then added dropwise to a batch containing 15 L of deionized water, rapidly increasing the pH to pH 9. The pH was maintained at this level during the addition, and a blue suspension began to form. Once the addition of the metal-containing solution was complete, the addition of the precipitate solution was stopped, and the resulting blue suspension was stirred at room temperature for an additional hour. The precipitate was removed from the suspension by filtration on a box filter press. The filter cake was washed with deionized water until the filtrate had a conductivity of <250 µS / cm. This filter cake was used to prepare the catalyst samples of Examples 4 through 6. It showed a Cu content of 40.8 mol%, a Zn content of 19.6 mol%, and an Al content of 39.6 mol%. Example 1
[0097] The filter cake of precursor A was dried at 120°C for 12 h. The filter cake was granulated and sieved through a 1 mm sieve, and then calcined at 450°C for 2 h in an intermittent rotary calciner, wherein the filter cake was heated at a heating rate of 300°C / h in the calciner. The calcined material was mixed with 2% by weight of graphite, compacted, and sheeted to produce sheets 4.8 mm wide and 3.2 mm high. Example 2
[0098] The filter cake of precursor A was suspended in deionized water to achieve a solids content of 18% by weight. The suspension was treated with a spray dryer with an inlet temperature of 280°C and an outlet temperature of 110°C. The spray-dried precursor was calcined in a continuous rotary calciner at 500°C and a mass flow rate of 300 g / h for 15 minutes. The calcined material was mixed with 2% by weight of graphite, compacted, and sheeted to produce sheets with a width of 4.8 mm and a height of 3.2 mm. Example 3
[0099] The same procedure as in Example 2 was applied, except that Cs2CO3 was added to the suspension prior to the spray drying step, resulting in a catalyst Cs content of 0.8% by weight. Example 4
[0100] The filter cake of precursor B was dried at 120°C for 12 h. The filter cake was granulated, sieved through a 1 mm sieve, and calcined at 450°C for 2 h in an intermittent rotary calciner, wherein the filter cake was heated at a heating rate of 300°C / h in the calciner. The calcined material was mixed with 2% by weight of graphite, compacted, and sheeted to produce sheets 4.8 mm wide and 3.2 mm high. Example 5
[0101] The filter cake of precursor B was suspended in deionized water to achieve a solids content of 18% by weight. The suspension was treated with a spray dryer with an inlet temperature of 280°C and an outlet temperature of 110°C. The spray-dried precursor was calcined in a continuous rotary calciner at 500°C and a mass flow rate of 300 g / h for 15 minutes. The calcined material was mixed with 2% by weight of graphite, compacted, and sheeted to produce sheets with a width of 4.8 mm and a height of 3.2 mm. Example 6
[0102] The same procedure as in Example 5 was applied, except that Cs2CO3 was added to the suspension prior to the spray drying step to produce a catalyst Cs content of 0.8% by weight. Comparative Example 1
[0103] The solution was provided by dissolving 14.16 mol Cu(NO3)2·2.5 H2O, 2.93 mol ZnO and 7.04 mol sodium aluminate in nitric acid solution to produce a volume of 20 L.
[0104] The metal-containing solution and 3.3M NaOH solution were then added dropwise to a batch container containing 15 L of deionized water. The pH increased rapidly and was maintained in the range of 9.5–10. Once the addition of the metal-containing solution was complete, the addition of the precipitate solution was stopped, and the resulting blue suspension was stirred at room temperature for an additional 3 hours. The precipitate was removed from the suspension by filtration on a box filter press. The filter cake was washed with deionized water until the filtrate had a conductivity of <250 µS / cm. The filter cake was dried at 120 °C for 6 hours and then calcined at 400 °C and a mass flow rate of 300 g / h for 15 minutes. It showed a Cu content of 60.5 mol%, a Zn content of 12.5 mol%, and an Al content of 27.0 mol%.
[0105] The resulting material was then mixed with 2% by weight of graphite, compacted, and sheeted to produce a sheet 0.48 mm wide and 3.2 mm high. Comparative Example 2
[0106] The solution was provided by dissolving 6.81 mol Cu(NO3)2·2.5 H2O, 8.88 mol ZnO, and 4.81 mol sodium aluminate in nitric acid solution to produce a volume of 20 L.
[0107] The metal-containing solution was heated to 90°C and added dropwise to a batch container containing a precipitate solution obtained by dissolving 1.350 kg of Na2CO3 in 26 L of deionized water, while the solution was vigorously stirred during the addition of the metal-containing solution.
[0108] During the addition of the metal-containing solution, the pH of the precipitate solution decreased from an initial 10 to 5 after the addition of the metal-containing solution was completed.
[0109] Once the metal-containing solution has been added, the resulting blue suspension is stirred at 90°C for an additional 30 minutes. Precipitates are removed from the suspension by filtration on a box filter press. The filter cake is washed with deionized water until the filtrate has a conductivity of <250 µS / cm. The filter cake is then calcined in a muffle furnace at 450°C for 24 hours. It shows a Cu content of 33.6 mol%, a Zn content of 44.1 mol%, and an Al content of 22.3 mol%.
[0110] The resulting material was then mixed with 2% by weight of graphite, compacted, and sheeted to produce a sheet 4.8 mm wide and 3.2 mm high.
[0111] Table 1 summarizes some characteristic data of the prepared catalysts.
[0112] Table 1: Properties of Examples 1 to 6 and Comparative Examples 1 and 2
[0113] Application Example 1
[0114] The catalysts of Examples 1 to 6 and Comparative Examples 1 and 2 were tested in the CO conversion reaction.
[0115] The sample was loaded into a reactor with an inner diameter of 2 mm at a dose of 220 mg, and was provided by grinding the corresponding flakes and separating them into sieve particle sizes of 200–300 μm.
[0116] The reaction was carried out at 25 barg pressure using a syngas feed (containing 3 vol% CO, 17 vol% CO2, 60 vol% H2, and 20 vol% N2) at a steam / gas ratio of 0.35, at different temperatures. It is possible to... Figure 1 and Figure 2 As seen in the comparative examples, the samples according to the present invention exhibit improved CO conversion and reduced inactivation rate.
Claims
1. A catalyst for LTS reaction, comprising an amorphous Cu-Zn-Al mixed oxide.
2. The catalyst according to claim 1, wherein it comprises domains of CuO, ZnO and Zn spinel, preferably Zn spinel of zinc spinel structure, as determined by pair distribution function (PDF) analysis.
3. The catalyst according to claim 1, wherein the catalyst is in the form of shaped catalyst bodies, preferably in the form of tabletted shaped bodies.
4. The catalyst according to claim 3, wherein the catalyst is in the form of a tableted shaped body having a side crushing strength of 40 to 250 N, preferably 80 to 220 N, more preferably 100 to 220 N, most preferably 150 N to 210 N.
5. The catalyst according to any one of the preceding claims, wherein the amount of Cu is in the range of 30 to 50 mol %, preferably 30 to 45 mol %, the amount of Zn is in the range of 15 to 45 mol %, preferably 20 to 40 mol %, and the amount of Al is in the range of 15 to 50 mol %, preferably 20 to 40 mol %, relative to the total amount of Cu, Zn and Al in the catalyst.
6. The catalyst according to any one of the preceding claims, wherein the phase content of CuO in weight percent determined by PDF analysis is in the range of 10 to 20, preferably in the range of 15 to 20, the phase content of ZnO in weight percent is in the range of 1 to 10, preferably in the range of 2 to 7, and the phase content of Zn spinel of zinc spinel structure in weight percent is in the range of 70 to 89, preferably in the range of 75 to 85.
7. A method for preparing a catalyst according to any one of the preceding claims, comprising the steps of: a) providing an aqueous solution comprising dissolved Cu, Zn and Al compounds, b) providing an aqueous solution comprising a carbonate, c) mixing the solution obtained in step a) and the carbonate solution obtained in step b) to obtain a mixture comprising a precipitate of mixed Cu-Zn-Al hydroxide-carbonate, d) aging the mixture obtained after step c), e) separating the precipitate from the solution and optionally washing and / or drying the precipitate, f) calcining the precipitate at a temperature in the range of 200 to 600°C, preferably in the range of 200 to 500°C, more preferably in the range of 300 to 500°C, most preferably in the range of 350 to 500°C, for a duration in the range of 15 minutes to 8 hours, preferably in the range of 0.5 to 6 hours, more preferably in the range of 1 hour to 6 hours.
8. The process according to claim 7, wherein the precipitate after step f) is shaped in step g) to give shaped catalyst bodies.
9. The method according to any one of claims 7 or 8, wherein the pH value after step c) is 8 or higher, preferably in the range of 8 to 9, more preferably 8.5 to 9.
10. An LTS reaction performed by using the catalyst according to any one of claims 1 to 6.
11. The LTS reaction according to claim 10, wherein the catalyst is reduced before use.
12. The LTS reaction according to claim 10 or 11, wherein a synthesis gas comprising CO, CO2 and H2 is used and wherein the CO content is 60% or less, preferably 20% or less, more preferably in the range of 0.1 to 20%.
Citation Information
Patent Citations
Heatproof Cu / ZnAl2O4 low temperature water gas converting catalyst
CN105214671A
Carbon monoxide conversion catalyst comprising composition for carbon monoxide conversion catalyst, and method of removing carbon monoxide using the same
JP2009241036A
Water gas shift catalyst
US6693057B1